Genetic and phenotypic characterization of the heat shock response in Pseudomonas putida. Issue 6 (10th October 2014) - Ito, Fumihiro; Tamiya, Takayuki; Ohtsu, Iwao; Fujimura, Makoto; Fukumori, Fumiyasu
Abstract Molecular chaperones function in various important physiological processes. Null mutants of genes for the molecular chaperone ClpB (Hsp104), and those that encode J‐domain proteins (DnaJ, CbpA, and DjlA), which may act as Hsp40 co‐chaperones of DnaK (Hsp70), were constructed from Pseudomonas putida KT2442 (KT) to elucidate their roles. The KTΔclpB mutant showed the same heat shock response (HSR) as the wild‐type, both in terms of heat‐shock protein (Hsp) synthesis (other than ClpB) and in hsp gene expression; however, the mutant was quite sensitive to high temperatures and was unable to disaggregate into thermo‐mediated protein aggregates, indicating that ClpB is important for cell survival after heat stress and essential for solubilization of protein aggregates. On the other hand, the KTΔdnaJ mutant was temperature‐sensitive, and formed more protein aggregates (especially of high molecular weight) upon heat stress than did KT. P. putida CbpA, a probable Hsp, partially substituted the functions of DnaJ in cell growth and solubilization of thermo‐mediated protein aggregates, and might be involved in the HSR which was regulated by a fine‐tuning system(s) that could sense subtle changes in the ambient temperature and control the levels of σ32 activity and quantity, as well as the mRNA levels of hsp genes.